2010
DOI: 10.2478/s11536-010-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Congenital herniation through the foramen Morgagni — clinical presentation, diagnosis and treatment in pediatric population

Abstract: AbstractCongenital Morgagni hernia is a rare entity, accounting for less than 1,5% of all types of congenital diaphragmatic hernias. The majority of Morgagni hernias are diagnosed late because patients can be asymptomatic or present with non-specific respiratory and gastrointestinal symptoms and signs. The medical records of all patients diagnosed with CMH and treated in our hospital were retrospectively reviewed for age at diagnosis, sex, site of hernia, clinical symptoms, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In none of the cases described in the literature, the hernial sac was resected, and only one horse had fluid accumulation in the dead space left after resolution of the hernia, without any significal clinical sequelae (Pauwels et al 2007). In humans, surgical removal of the hernial sac is controversial and there is no consensus about the benefit of this procedure (Andelka et al 2011). Some authors recommend sac excision because it may decrease the chance for symptomatic fluid collection and reduce recurrence rate, because the sac itself can act as a lead point for recurrent herniation.…”
Section: Discussionmentioning
confidence: 99%
“…In none of the cases described in the literature, the hernial sac was resected, and only one horse had fluid accumulation in the dead space left after resolution of the hernia, without any significal clinical sequelae (Pauwels et al 2007). In humans, surgical removal of the hernial sac is controversial and there is no consensus about the benefit of this procedure (Andelka et al 2011). Some authors recommend sac excision because it may decrease the chance for symptomatic fluid collection and reduce recurrence rate, because the sac itself can act as a lead point for recurrent herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a period of medical stabilization and delay in repair was proposed in an attempt to improve the general condition of the newborn with HDC. The survival rate of newborns with CDH ranges from 60 to 90% through the use of physiological treatment strategies including gentle ventilation techniques, high-frequency ventilation, cardiovascular pharmacological support, and extracorporeal membrane oxygenation (ECMO) with gradual improvement in survival 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiography is usually the study in which the defect is identified during the neonatal period, where a structure is identified behind the cardiac silhouette and the lateral projection allows this structure to be located in the retrosternal area. There may be other alterations or syndromes associated with Morgagni's diaphragmatic defect, among which are intestinal malrotation, esophageal atresia, omphalocele, trisomy 21, 18, and 13, Beckwith-Wiedemann syndrome, and Goldenhar syndrome 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The Morgagni hernia accounts for approximately 1.5% of all congenital diaphragm hernia (CDH) cases [2,3]. In most cases, Morgagni hernias are diagnosed late due to the fact that patients can be asymptomatic or can display vague gastrointestinal and respiratory signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%